STRATEGI MITIGASI RISIKO UNTUK MENINGKATKAN RETURN PERUSAHAAN START-UP DALAM EKONOMI DIGITAL - Amelia, Corrinna Salsabila (Jurnal Ekonomi dan Bisnis (EK&BI), 2025)
Business paradigm shifts caused by advances in digital markets and technology bring both opportunities and challenges. The purpose of this research is to identify the importance of risk mitigation strategies in increasing the returns of startup companies in the digital economy era. In addition, this research emphasizes the importance of risk management, especially with historical financial statement data such as Return on Investment (ROI), in assessing the performance and prospects of startup investments. This research uses a qualitative approach with data collection techniques using literature studies. The Miles & Huberman model was used for data analysis, including phases, data collection, data reduction, data presentation and conclusion. The results showed that the risks commonly faced by startup companies in this digital economy era include financial risk, technology risk, market risk, regulatory risk, and human resource risk. A good risk mitigation strategy is the key to achieving sustainable growth and optimal returns, so as to increase investor confidence to reduce losses and encourage sustainable growth. In addition, startups that carry out proactive risk management can remain competitive, creative, and have the ability to provide optimal value and profit in the midst of current digital market dynamics.